Idiopathic nephrotic syndrome: a clinical approach. Issue 7 (July 2022) - Norman, Karen; Christian, Martin
Abstract: Children with new-onset nephrotic syndrome invariably present to general paediatrics in the first instance. Many with known nephrotic syndrome under the care of a paediatric nephrologist will present to local services with complex relapses. Using a case-based approach, this review aims to equip the general paediatrician with the skills: to assess and manage a child with a new presentation of nephrotic syndrome, to identify the complications associated with the nephrotic state, to choose the most appropriate steroid regimen and to identify those patients who should be referred to a paediatric nephrologist. We focus on the management of steroid-sensitive nephrotic syndrome (SSNS), the most common diagnosis in children presenting with nephrotic syndrome. We also discuss aspects of management of nephrotic syndrome relevant to the COVID-19 pandemic. Additionally, by the end of the article, the reader should have a basic understanding of the underlying pathophysiology of nephrotic syndrome and its resultant complications.